Inbreeding Depression and Genetic Diversity of S1 Lines Corn Plants Under Drought Stress Conditionson Dry Land - I Wayan Sudika; I Wayan Sutresna; Dwi Ratna Anugrahwati; Ni Wayan Sri Suliartini; I Wayan Suana (Jurnal Penelitian Pendidikan IPA, 2024)
Selfing was carried out on the F2 population of corn plants and the S1 line was produced. Selfing is carried out to form pure lines in order to create hybrids. The aim of the research was to determine the magnitude of inbreeding depression, genetic diversity and heritability of leaf angle trait, yield and harvest age of the S1 line of corn plants under drought stress conditions in dry land. The experiment was carried out from March to June 2023 in Gumantar village, North Lombok district. The design used was a randomized block design, two replications. The number of treatments was 31, namely 30 S1 lines and an F2 population. Plantings are given heavy stress. Observed variables include flowering, growth, harvest age, yield components and yield. The level of inbreeding depression is based on the F2 population and is expressed as a percent. Genetic diversity is calculated based on the results of analysis of variance at a significance level of 5 percent. The results showed that inbreeding depression in leaf angle and harvest age of the S1 lines were relatively low; while the yield is classified as high. Broad categories of genetic diversity were obtained in the yield; while the leaf angle and harvest age are relatively narrow. Broad sense heritability was relatively high in the yield; while the leaf angle is classified as medium and the harvest age is relatively low. The selection of S1 lines should be based on yield, namely lines that have the same yield as the F2 population.